The Reciprocal Paradigm of TafsÄ«r al-Miá¹£bah and TafsÄ«r al-Taá¸¥rÄ«r wa al-TanwÄ«r on Surah al-Baqarah verse 222 about Menstruation Blood - Millati, Halya (Sawwa: Jurnal Studi Gender, 2021)
Misogynistic interpretation of women on their menstruation period as "a dirt" that emerged from pre-Islamic Arab society and some classical commentators opened vast space for critics. One of the critics is the interpretation of al-Baqarah verse 222 as an effort to maintain reproduction health. This paper compares the interÂpretation of al-Baqarah verse 222 in TafsÄ«r al-Miá¹£baá¸¥ by Quraish Shihab, and TafsÄ«r al-Taá¸¥rÄ«r wa al-TanwÄ«r, by Ibn 'Ä€shÅ«r. These two interpretations are taken because they have relatively similar interpretations when interpreting al-Baqarah verse 222, even though the author's historical setting is different. With the comparative method and theory of qirÄâ€™ah mubÄdalah, this paper answers how the interpretation of Quraish Shihab and Ibn 'Ä€shÅ«r on al-Baqarah verse 222 and how the linearity of that interÂpretation is. This paper finds, firstly, that Quraish Shihab and Ibn 'Ä€shÅ«r agree in interpreting al-Baqarah verse 222 with the prohibition of intercourse, while the wife is on her period to maintain reÂproduction health and interpret adhÄ as an uncomfortable condition. It's just that Quraish Shihab defines adhÄ as disturÂbance, while Ibn 'Ä€shÅ«r means al-á¸arr (injury or danger). Secondly, the two interpretations use a reciprocal paradigm with the evidence of the meaning of adhÄ as a disturbance or risk that can be occurred both women and men.